2021
DOI: 10.1039/d1fo01156a
|View full text |Cite
|
Sign up to set email alerts
|

Cross-kingdom regulation by dietary plant miRNAs: an evidence-based review with recent updates

Abstract: As non-coding RNA molecules, microRNAs (miRNAs) are widely known for their critical role in gene regulation. Recent studies have shown that plant miRNAs obtained through dietary oral administration can survive...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 108 publications
0
21
0
Order By: Relevance
“…Additionally, accumulating evidence indicates that sRNAs can be transferred within cells and tissues and even across species (66) and miRNAs from diet have been proposed to play a role on disease prevention (67,68). Additionally, several authors report that dietary-miRNAs can be absorbed with diet and reach their target mRNAs, both for animal (64,69) and plant (22,65) foodstuffs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, accumulating evidence indicates that sRNAs can be transferred within cells and tissues and even across species (66) and miRNAs from diet have been proposed to play a role on disease prevention (67,68). Additionally, several authors report that dietary-miRNAs can be absorbed with diet and reach their target mRNAs, both for animal (64,69) and plant (22,65) foodstuffs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the latest evidence shows that dietary plant miRNAs can not only be absorbed in the intestine, but also be absorbed and packaged by gastric epithelial cells and then secreted into the circulatory system. The former, leads to consider miRNAs as biologically active plant-derived in a similar way that phytochemicals and, therefore, potentially responsible of food functionality (22).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are a class of small (17-24 nucleotides) and noncoding RNAs with abilities to inhibit mRNA translation (36,37). The latest evidence shows that plant miRNA can be absorbed in the intestine and secreted into the circulatory system (38). The previous report had shown that PELNs deliver miRNA to animals, target mammalian mRNA, and have the potential to mediate a specific tissue response (24,39).…”
Section: Composition Of Pelnsmentioning
confidence: 99%
“…The previous report had shown that PELNs deliver miRNA to animals, target mammalian mRNA, and have the potential to mediate a specific tissue response (24,39). In addition, miRNA in PELNs can be taken up by bacteria and alter microbiome composition and host physiology (28,38,40). But the functions and mechanisms of miRNAs in PELNs are still unknown.…”
Section: Composition Of Pelnsmentioning
confidence: 99%
“…The other obvious question concerns the potential of plant miRNAs to become new natural medicine products ( Lukasik and Zielenkiewicz, 2016 ). This subject was recently extensively reviewed e.g., ( Sanchita et al, 2018 ; Jia et al, 2021 ; Li et al, 2021 ; Samad et al, 2021 ; Winkle et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%